Bioactivity, Efficacy, and Safety of a Wound Healing Ointment With Medicinal Plant Bioactives: In Vitro and In Vivo Preclinical Evaluations - Floriano, Juliana Ferreira [UNESP]; Rodrigues, Daniel; Ohara, Rie; Almeida, Nara Lígia Martins; Lara, Vanessa Soares; Sartorelli, Patricia; Graeff, Carlos Frederico de Oliveira [UNESP]; Grecco, Simone dos Santos; González, Alejandra Hortencia Miranda; D’Alpino, Paulo Henrique Perlatti [UNESP] (Wiley, 2025)
Chronic wounds have a significant impact on patients’ quality of life, necessitating the management of pain, infection, bleeding, and emotional challenges. Debridement, which involves the removal of nonviable tissue, is crucial for promoting wound healing. In addition to surgical methods, cost-effective alternatives such as local solutions and ointments with biological properties have been explored. The use of natural compounds with anti-inflammatory, antibacterial, and collagen-synthesizing abilities holds promise for wound healing. This in vitro and in vivo preclinical study aimed to assess the safety and effectiveness of a wound healing ointment containing bioactive ingredients derived from medicinal plants (extracts, essential oils, and vegetable oils). The chemical composition of the ointment was characterized using Fourier transform infrared (FTIR) spectroscopy to gain insights into its synergistic action. Preclinical tests were conducted following standardized protocols. FTIR analysis revealed similarities between the product’s spectrum and that of bioactive compounds. The in vitro tests demonstrated that all formulations of the ointment induced no cell death, DNA damage, or acute toxicity in cell cultures (p < 0.05). No lethal dose was observed, indicating the safety of the ointment at all concentrations. The ointment also stimulated a notably more organized, significantly higher collagen production compared to control groups (p < 0.05). In vivo preclinical analyses also demonstrated no adverse responses being effective in the healing process compared to the control group (silver sulfadiazine) in terms of wound contraction and ulcer re-epithelization (p < 0.05). Significantly higher means of wound contraction were observed in the groups treated with the bioactive-containing ointment when compared to both the positive control group (sulfadiazine) and the control untreated groups (p < 0.05). The regenerative ointment exhibited excellent biocompatibility and bioactivity in in vitro and in vivo studies, contributing to the development of innovative and sustainable wound management therapies.
Keywords: biocompatibility; chronic wounds; natural compounds; preclinical tests; wound care